Modelling Porous Cementitious Media with/without Integrated Latent Heat Storage: Application Scenario - Mona Nazari Sam; Jens Schneider; Holger V. Lutze (Energies, 2023)
This paper presents a methodological approach for the evaluation of the thermal behavior of cementitious porous media with/without integrated latent-heat thermal energy storage (LHTES). To achieve this goal, the Lewis-Nielsen model has been calibrated to predict the insulation properties of mineralized foamed concretes. Two pore-related microstructural fitting parameters, A and Φm, are presented according to the available data in the literature. In this regard, new findings are implemented for the classification of pore structure and prediction of the homogenized thermal conductivity of two-phase cementitious foams with or without phase change materials. The calibration and predictive analyses have been extended to a wide range of experimental data, including variation of binder types, porosities, and latent components. The presented analytical approach appears to agree well with experimental results and can be employed in the design of two-phase mineral foam materials. Then, to assess the thermal behavior of the predicted insulating envelopes, a one-dimensional (1D) enthalpy-based model is used which combines Fourier’s law of heat conduction, the first law of thermodynamics, Lewis-Nielsen conductivities, and the mixture theory for LHTES additions. The results demonstrated the importance of volumetric heat capacity for the thermal inertia of building envelopes.